Sasakawa Ryoichi : A life - Sato, Seizaburo (EastBridge, 2006)
This biography covers the 96 years of Sasakawa's remarkable life, from rural village boyhood to Imperial Army conscript, savvy investor, fervent anti-Communist, political fixer, business magnate, and beyond. His dedication to public interest is traced as a constant throughout his life, rather than a postwar shift in ideology-much like the ambition and self-belief that drove him forward to such success.